The Palmaris Longus and Its Association with Carpal Tunnel Syndrome - Boltuch, Andrew D.; Marcotte, Michael A.; Treat, Christopher M.; Marcotte, Anthony L. (Journal of Wrist Surgery, 2020)
Background The palmaris tendon inserts into the palmar fascia and is positioned in close association with the transverse carpal ligament. Loading of this tendon has been demonstrated to increase carpal tunnel pressures.Purpose The purpose of this study was to determine if a relationship exists between the palmaris tendon, carpal tunnel syndrome (CTS), and handedness. The sensitivity, specificity, positive predictive value, and negative predictive value for Schaeffer's test were calculated.Methods A retrospective review of patient charts undergoing endoscopic carpal tunnel release was performed. Rates of palmaris longus agenesis (PLA) were compared to a population matched data set. Statistical analysis was performed using a one-proportion z-test. Schaeffer's test for the palmaris longus tendon was performed on all patients and compared to intraoperative confirmation.Results A total of 520 carpal tunnel releases were performed in 389 consecutive patients. The frequency of PLA in this surgical cohort was significantly lower compared to the population matched dataset. No correlation between handedness and laterality of CTS or PLA was found. Schaeffer's test was evaluated to yield sensitivity (93.6%), specificity (100%), positive predictive value (100%), and negative predictive value (50.8%).Conclusion The palmaris tendon was more prevalent in a population of patients undergoing carpal tunnel release. These findings can be used to provide further insight into the pathophysiology of CTS. While Schaeffer's test was accurate in detecting the palmaris longus tendon, a negative test was frequently incorrect. Further imaging is recommended in patients with a negative Schaeffer's test when the palmaris longus is desired for surgical utilization.Level of Evidence This is a Level III, prognostic study.
Keywords: carpal tunnel syndrome; congenital absence; endoscopic carpal tunnel release; palmaris longus tendon; median nerve compression